Avoidance Responses of Minke Whales to 1-4 kHz Naval Sonar: - Kvadsheim,P.H.; DeRuiter, S.; Sivle, L.D.; Goldbogen, J.; Hansen, R.R.; Miller, P.; Lam, F.P.A.; Calambokidis, J.; Friedlaender, A.; Visser F; Tyack, P.; Kleivane, L.; et al. (2017)
Minke whales are difficult to study and little information exists regarding their responses to anthropogenic sound. This study pools data from behavioural response studies off California and Norway. Data are derived from four tagged animals, of which one from each location was exposed to naval sonar signals. Statistical analyses were conducted using Mahalanobis distance to compare overall changes in parameters summarising dive behaviour, avoidance behaviour, and potential energetic costs of disturbance. Our quantitative analysis showed that both animals initiated avoidance behaviour, but responses were not associated with unusual dive behaviour. In one exposed animal the avoidance of the sonar source included a 5-fold increase in horizontal speed away from the source, implying a significant increase in metabolic rate. Despite the different environmental settings and exposure contexts, clear changes in behaviour were observed providing the first insights into the nature of responses to human noise for this wide-ranging species.